Realitys and misbeliefs about microhabitat preferences of the weather loach (Misgurnus fossilis) (Preliminary results) - Fazekas, Gergely (Acta Agraria Debreceniensis, 2008)
I studied in this research, the weather loach (Misgurnus fossilis). This fish was in Europe common, but in our days desolated from several area. In Europe this fish was protected by law, and it got into the II. appendix of Habitat Directive. Although is it protected, the reserarchers don’t know too much about it’s optimal habitat needs. My aim was, to specify some habitat parameters of the weather loach. That’s why I analyzed the impression of some parameters, whichs I measured in an optimal habitat for weather loach.